Terms of Reference for Conducting a Situational Analysis of Climate and Gender Inequity Hotspots - CGIAR GENDER Impact Platform (CGIAR GENDER Impact Platform, 2022)
The CGIAR GENDER Platform through the Evidence Module wishes to engage a partner organisation to conduct a situational analysis of gender inequality, gender dynamics, agricultural and food system transformation, and challenges related to climate change using methods and indicators proposed by the GENDER Platform team for selected regions in Bangladesh and Zambia that have been identified as climate-gender inequity hotspots. Additionally, the partner organisation will be expected to list a number of interventions in these regions by research or development projects/programs/organizations, ideally ongoing, soon to be launched, or towards the end in the design stage, which offer an opportunity to combine gender transformative interventions and experimentally test the options to optimise gender equality and food system outcomes. The partner organisation will work closely with the GENDER Platform team during this process. This Terms of Reference details the said assignment and outlines the requirements for the application.